2015
DOI: 10.1016/j.juro.2014.07.104
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Comparison of Urolithiasis Scoring Systems Used in Percutaneous Kidney Stone Surgery

Abstract: All scoring systems and the stone burden equally predicted stone-free status. The Guy and S.T.O.N.E. nephrolithometry scores were associated with estimated blood loss and length of stay. A single scoring system should be adopted to unify reporting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
107
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(122 citation statements)
references
References 26 publications
11
107
0
4
Order By: Relevance
“…Labadie et al 12 compared each system in the same cohort to determine which was more predictive of surgical success. They concluded that all classification systems could equally predict stone-free rate.…”
Section: Discussionmentioning
confidence: 99%
“…Labadie et al 12 compared each system in the same cohort to determine which was more predictive of surgical success. They concluded that all classification systems could equally predict stone-free rate.…”
Section: Discussionmentioning
confidence: 99%
“…All of the factors listed are ranked between 0-100, with a total score obtained ranging between 0-350, with a probability of SFR from 30 to 90%, depending on the total sum obtained. [2] Recently, Labadie et al [9] , evaluated and compared the three scores, finally concluding that all systems similarly predict the SFR, and a single and simple scoring system should be adopted to unify the reporting like the GSS. Bozkurt et al [10] recently compared in a retrospective, single-center study the GSS and the CROES (Clinical Research Office of Endourological Society) nephrolithometric nomogram, concluding that both scorings systems equally predict the postoperative outcomes of PCNL, including SFRs, overall complications, blood loss and operative times.…”
Section: Introductionmentioning
confidence: 99%
“…and CROES scores also found to be associated with complications), although cross-comparative studies have been fewer [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The only systematic review concluded with ambiguity over the clear superiority of any one system and recommended further validation studies [23].…”
Section: Introductionmentioning
confidence: 99%
“…All that can be proved is whether scores are significantly higher or lower for outcomes other than SFR (which does not really aid in decision making in terms of providing a risk estimate or clinical cut-off point) or break the results of the nomogram score into arbitrary categories (with doubtful clinical relevance and chance of introducing confounding if categories are uneven; as larger categories may inherently carry larger risk) and treat it like a ordinal score [19,21]. 2 Ordinal scores do grade calculus complexity based on radiological characteristics.…”
Section: Introductionmentioning
confidence: 99%